1984
DOI: 10.1111/j.1365-2761.1984.tb01198.x
|View full text |Cite
|
Sign up to set email alerts
|

The non‐specific activation of rainbow trout, Salmo gairdneri Richardson, complement by Aeromonas salmonicida extracellular products and the correlation of complement activity with the inactivation of lethal toxicity products

Abstract: The possible mechanism of inactivation of the toxieity of Aeromonas salmonicida extracellular products (ECP) by normal rainbow trout serum was investigated using juvenile rainbow trout. ECP was prepared from culture supernatant by an acetone precipitation method. The ECP was incubated with normal rainbow trout serum at 20°C for 2 h, and the interrelationship between ECP proteolytic activity and immune complex-initiating, haemolytic complement activity (CH50) of normal serum against antibody-sensitized goldfish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…In salmonids, cogent observations have been reported with the parasite C. salmositica (Wehnert & Woo, 1980;Bower & Evelyn, 1988), Vibrio anguillarum (Trust et al, 1981), and A. salmonicida (Sakai, 1984). In all cases, inactivation of the pathogen or of its virulence factors were e#ective in the absence of specific antibodies, and such was the case, too, in our experiments.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In salmonids, cogent observations have been reported with the parasite C. salmositica (Wehnert & Woo, 1980;Bower & Evelyn, 1988), Vibrio anguillarum (Trust et al, 1981), and A. salmonicida (Sakai, 1984). In all cases, inactivation of the pathogen or of its virulence factors were e#ective in the absence of specific antibodies, and such was the case, too, in our experiments.…”
Section: Discussionsupporting
confidence: 71%
“…Evidence for the existence of the alternative pathway in salmonids was reported by Nonaka et al (1981), Iida & Wakabayashi (1983) and Sakai (1983). Although its e$cacy against virulent organisms has sometimes been questioned (Ourth & Bachinski, 1987;Jenkins et al, 1991), it is suspected to play a protective role in serious infections caused by the flagellate Cryptobia salmositica (Wehnert & Woo, 1980;Bower & Evelyn, 1988) and the bacterium Aeromonas salmonicida (Sakai, 1984).…”
Section: Introductionmentioning
confidence: 91%
“…In the present study, bactericidal activity of eel serum was decreased by the treatment with protease (Table 4). The same phenomenon was reported by SAKAI (1984), who demonstrated that hemolytic activity (CH50) of rainbow trout serum was considerably reduced by treatment with A. salmonicida protease. The depletion of complement induced by the protease may play a part in increasing susceptibility of Japanese eel to V. anguillarum (Table 1).…”
Section: Discussionsupporting
confidence: 62%
“…Recently various virulence factors of Aeromonas salmonicida, the causative agent of fish furun culosis, have been investigated and the roles of its protease in the pathogenesis of the infection were also examined (SAKAI, 1984(SAKAI, , 1985bTITBALL, 1985;FYFE et al, 1986). These volumi nous studies were thought to be carried out due to the incompletion of effective vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the alternative pathway can also be mediated in vitro by extracellular products from the salmonid pathogen Aeromonas salmonicida (Sakai, 1984a).…”
Section: Introductionmentioning
confidence: 99%